Persistência do forame de Huschke: Um estudo tomográfico - Reis, Henrique Nogueira; Carvalho, Antonio Carlos Pires; Leite, Horácio Faig [UNESP]; De Mello, Rossana Corbo Ramalho; Xavier, Sergio Salles (FapUNIFESP (SciELO), 2006)
OBJECTIVE: To evaluate the persistency of foramen of Huschke by means of computed tomography study of the ear region and approaching important clinical aspects related to the presence of this anatomical anomaly. MATERIALS AND METHODS: Two examiners have analyzed the whole tympanic portion of temporal bone in 150 bilateral computed tomography studies of the ear region, searching for foramen of Huschke presence or absence. RESULTS: The mentioned anatomical anomaly was found in 17 cases (11.3%), 13 patients (76.5%) being female and four (23.5%) male. This higher female incidence is statistically confirmed. CONCLUSION: Ear and/or temporomandibular joint specialists should turn their attention to the persistency of foramen of Huschke.
Persistent foramen of Huschke: A tomographic study
Keywords: Computed tomography; Foramen of Huschke; Temporal bone - Formation and development